Biodeterioration of mortars exposed to sewers in relation to microbial diversity of biofilms formed on the mortars surface. (May 2018) - Lors, Christine; Aube, Johanne; Guyoneaud, Rémy; Vandenbulcke, Franck; Damidot, Denis
Abstract: Strong deterioration of concrete in sewer systems is mainly due to microorganisms and especially to sulfur-oxidizing bacteria. Mortars made either with ordinary Portland cement (OPC) or calcium aluminate cement (CAC) were exposed in a waste water collector for five years. Mortar microstructure observed by microscopy reported a larger thickness of the degraded zone for OPC mortar. Taxonomic identification of bacterial communities performed on biofilms collected at the mortar surface reported similar bacterial diversities, but strong differences of relative abundance. A greater neutrophilic sulfur-oxidizing bacterial (NSOB) activity was observed for OPC mortar certainly in conjunction with its larger acid neutralization capacity. Thus, CAC mortar was less biodeteriorated than OPC mortar as less NSOB were able to settle on its surface in relation with its specific microstructure. The results of the reported field experiments have been compared with bioleaching laboratory experiments performed on identical mortars in the presence of Halothiobacillus neapolitanus as NSOB. As the deterioration mechanisms involved were similar, an acceleration factor with respect to the rate of in situ biodeterioration was determined for laboratory experiment. Highlights: CAC mortars placed 5 years in sewers were less deteriorated than OPC mortars. Less sulfur-oxidizing bacteria were able to settle on the surface of CAC mortars. Results have been compared to similar mortars subjected to bioleaching assay. An acceleration deterioration factor was defined for bioleaching assays.